2010
DOI: 10.1029/2008jb006160
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic properties of gas hydrate–bearing consolidated sediments and experimental testing of elastic velocity models

Abstract: [1] Although elastic velocities (V p , V s ) can be used to assess the distribution and concentration of marine gas hydrates in situ and several existing models relate hydrate saturation to acoustic velocity, the accuracy of these models is uncertain because of the difficulty in determining hydrate saturations and velocities of intact hydrate-bearing sediments. In this paper, the acoustic properties of gas hydrate-bearing consolidated sediments were investigated experimentally. Hydrate saturation (S h ) and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 43 publications
1
34
1
Order By: Relevance
“…The geophysical experimental apparatus in the Gas Hydrate Laboratory of Qingdao Institute of Marine Geology (GHL-QIMG) [Ye et al, 2005Hu et al, 2010] can simulate in situ pressure and temperature conditions conducive to hydrate formation (Fig. 4).…”
Section: Synthesized Methods Of Hydrated Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The geophysical experimental apparatus in the Gas Hydrate Laboratory of Qingdao Institute of Marine Geology (GHL-QIMG) [Ye et al, 2005Hu et al, 2010] can simulate in situ pressure and temperature conditions conducive to hydrate formation (Fig. 4).…”
Section: Synthesized Methods Of Hydrated Sedimentsmentioning
confidence: 99%
“…For example, Regalado et al [2003] proposed a empirical equation for calculating water contents of volcanic soils; Wright et al [2002] found the relationship between dielectric constants and water contents of hydrate-bearing sediments. Thereafter, TDR was effectively used to measure hydrate pore saturations of the hydrated sediments Hu et al, 2010]. Fig.…”
Section: Tdr Techniquementioning
confidence: 99%
“…In these domains the combined Eqs. (1) and (2) reduce to the quasi- static, linearized Navier-Stokes' equations for the laminar flow of a Newtonian fluid (e.g., Jaeger et al, 2007).…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Additionally, the recovery of unaltered natural GH samples is hampered due to their fast decomposition under ambient conditions. Therefore, various researchers have attempted to mimic the natural environment of GH-bearing sedimentary matrices in laboratory experiments (Berge et al, 1999;Ecker et al, 2000;Dvorkin et al, 2003;Yun et al, 2005;Spangenberg and Kulenkampff, 2006;Priest et al, 2006Priest et al, , 2009Best et al, 2010Best et al, , 2013Hu et al, 2010;Li et al, 2011;Zhang et al, 2011;Dai et al, 2012;Schicks et al, 2013). The results of this collective effort established a number of conceptual models for the role of GH embedded in its sedimentary matrix (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Different habits, distributions and saturation of gas hydrate crystals in the pore space affect the physical properties of the hydrate-bearing sediment (Priest et al, 2005;Waite et al, 2004). As the recovery of unperturbed natural methane hydrates is very difficult due to their fast decomposition under ambient conditions, a number of researchers have attempted to recreate the natural environment of gas hydrate in sedimentary matrices via laboratory experiments (Berge et al, 1999;Best et al, 2010Best et al, , 2013Dai et al, 2012;Dvorkin et al, 2003;Ecker et al, 2000;Hu et al, 2010;Li et al, 2011;Priest et al, 2006Priest et al, , 2009Spangenberg and Kulenkampff, 2006;Yun et al, 2005;Zhang et al, 2011). This collective effort eventually leads to a set of idealized micro-structural models (Fig.…”
Section: Introductionmentioning
confidence: 99%